The gilded shroud eaudiobook - Bailey, Elizabeth (Lady Fan Mystery, 2019)
When a murder is committed, a lady's companion finds herself in the role of amateur sleuth . . . 1789, London: When Emily Fanshawe, Marchioness of Polbrook, is found strangled in her bedchamber, suspicion immediately falls on those residing in the grand house in Hanover Square. Emily's husband—Randal Fanshawe, Lord Polbrook— fled in the night and is chief suspect—much to the dismay of his family. Ottilia Draycott is brought in as the new lady's companion to Sybilla, Dowager Marchioness, and soon finds herself assisting younger son Lord Francis Fanshawe in his investigations. Can Ottilia help clear the family name? Does the killer still reside in the house? Or could there be more to the mystery than meets the eye?